Teknik Permainan Dan Penyajian Lagu When A Man Loves Woman Karya Percy Sledge Pada Instrumen Alto Saxophone - Hot Parulian Sitohang; Junita Batubara; Brian Harefa (Journal on Education, 2023)
This study discusses the technique of playing the alto saxophone on the song When a Man Loves a Woman by Percy Sledge. This song has been played by many saxophone players including: Galaxsea Band Cancun, Angelo Torres, Paulo Franco, Richard Elliot. Presentation of the song When a Man Loves a Woman the author uses a band format with breathing techniques, staccato techniques, growl techniques, and altissimo techniques. The author discusses the level of difficulty experienced by the author, especially in breathing techniques and growl techniques. At the end, the author explains the presentation of the song When a Man Loves a Woman during the recital.